"Own store" vision for Finnish co-op: Retailer stays true to its core values. Issue 1 (11th January 2016) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – The case-study article illustrates how a Finnish grocery retailer introduced a compelling alternative strategy, based on co-operative principles, to transform the organization's fortunes in the face of increasing competition from rivals with global buying power. The study presents the four focal tasks of the vision and concludes with five practical guidelines for executives. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.